PENGARUH KONSELING KB TERHADAP PENGETAHUAN DAN SIKAP PASANGAN USIA SUBUR DALAM MEMILIH KB YANG TEPAT - Novi Wulansari; Erlina Sari (Maternal Child Health Care, 2023)
Difficulties in choosing the type of contraception are experienced by many prospective family planning acceptors. Caused by ignorance about the various advantages and disadvantages or side effects of each method of contraception. Efforts to overcome these problems require an effort to provide counseling or Information and Education (KIE) to each prospective family planning acceptor. The purpose of this study was to determine the effect of family planning counseling on knowledge and attitudes of couples of childbearing age in choosing the right family planning program in the work area of the Desa Baru Health Center in 2022. This type of research was Quasi Experiment with a Two Group Pretest Test-posttest design. This research was conducted from January to June 2022 in the working area of the Desa Baru Health Center. The population of this study were all couples of childbearing age in the New Village Health Center Working Area in 2022 as many as 2,083 people. The research sample was 96 people with purposive sampling technique. Collecting data using a questionnaire sheet. The results of this study indicate that the average knowledge of mothers before the intervention is 9.01, the average after the intervention is 10.00. The mean attitude of the mother before the intervention was 41.48, after the intervention was 43.47. The results of the paired t test showed that there were differences in knowledge before and after family planning counseling (p value = 0.000) and there were differences in attitudes before and after counseling (p value 0.000). It can be concluded that there is an effect of family planning counseling on the knowledge and attitudes of couples of childbearing age in choosing the right family planning. It is recommended that health workers always provide counseling to couples of childbearing age related to the use of contraceptives, so that government programs run well